A Study and Comparison of the Preparation of Gadolinium Aluminate Nanoparticles Using γ-Irradiated and Unirradiated Precursors - Tehani I. Al-Muhimeed; Abdullah A. Al-Kahtani; Refaat M. Mahfouz; Mujeeb Khan; M. Rafiq H. Siddiqui (Advances in Materials Science and Engineering)
The effects of γ-irradiation and the application of different precursors on the formation of gadolinium aluminate (GdAlO3) nanoparticles (NPs) have been studied in detail. GdAlO3 NPs were prepared by using different gadolinium-based precursors including gadolinium acetate (Gd(CH3COO)3·4H2O) and gadolinium nitrate (Gd(NO3)3·6H2O), while Al2O3 and Al(NO3)3·9H2O were used as the source of Al3+. The preparation of GdAlO3 was carried out by two different methods, solid-state reaction and sol-gel process. To study the effect of γ-irradiation, both irradiated and unirradiated Gd(CH3COO)3·4H2O have been tested for the preparation of gadolinium aluminate (GdAlO3). Notably, Gd(CH3COO)3·4H2O did not produce GdAlO3 in both solid-state and sol-gel processes even after optimizing various parameters, including the application of γ-irradiation. However, single-phase nanocrystalline GdAlO3 NPs were successfully obtained from the reaction of gadolinium nitrate Gd(NO3)3·6H2O and Al(NO3)3·9H2O by a sol-gel process. The formation of NPs has been confirmed by X-ray diffraction analysis (XRD) and Fourier-transform infrared (FT-IR) spectroscopy. The results indicate towards the formation of an orthorhombic perovskite structure of GdAO3 in the Pbnm space group. Transmission electron microscopy (TEM) has been employed for the particle-size analysis, which revealed the formation of spherical-shaped nanoparticles with the size range of 50–70 nm. Surface morphology of the sintered pellet was obtained from high-resolution scanning electron microscopy (HR-SEM). Besides, the effect of irradiation with γ-rays on the quality of resultant NPs has also been studied.